Study Of Behaviour-based Navigation for Indoor Mobile Robot - Ue Wei, Tan (2018)
A mobile robot with a behaviour-based navigation system is where a robot relies on sensor inputs to control the locomotion of the mobile robot while navigating along an unknown path. The aim of this project is to study a behaviour-based navigation algorithm when implemented in a basic robot for navigation in an indoor environment. The mobile robot should be able to navigate from one point to another autonomously. As part of the behaviour-based autonomous navigation system, three behaviours have been developed for the mobile robot. The behaviours include the wall follower behaviour, obstacle avoidance behaviour and the move to goal behaviour. The wall follower behaviour is mainly controlled using the PID controller. The developed behaviours were then tested in a track consisted of 5 types of junctions which are the left turn, right, turn, dead-end, 3-way and 4-way junctions. 10 trials have been done on each junction in order to observe the success rate of the mobile robot reacting to the approached junction. Throughout the experiment, it was observe that the mobile robot is able to navigate through the left turn, right turn and dead-end junctions with 100% success rate. However, the success rate when the robot encounters a 3-way and 4-way junction is only 80% and 60% respectively. For future work, individuals should look into using faster sensors like the laser distance sensors as light travels faster than sound and could possibly improve the performance of this navigation system.